A simple method for monitoring dog leash compliance behavior in parks and natural areas. (April 2015) - Leung, Yu-Fai; Walden-Schreiner, Chelsey; Conlon, Katharine; Miller, Anna B.
Abstract: This article presents a monitoring protocol for dog leash compliance designed with public participation, mobile technology and flexible platforms in mind. We describe the protocol development and illustrate data utility by comparing results across three trail surface types. Implemented at an urban nature park in North Carolina, pilot tests indicated a high level of inter-observer reliability (>86%) for all variables. The consistency was improved further by refining the measures and the observation procedure. A total of 169 dogs were observed during the study period with an overall compliance rate of 87%. Significantly lower compliance was found on the woodchip and unpaved trail sections (71–74%) than the paved section (99%). Our results suggest this approach may serve as a reliable protocol for monitoring a common and important impact issue. Lessons learned are shared to stimulate further advancements and applications of technology in participatory monitoring of this and other indicators of sustainable recreation.